2019
DOI: 10.1109/access.2019.2948405
|View full text |Cite
|
Sign up to set email alerts
|

STELA: A Real-Time Scene Text Detector With Learned Anchor

Abstract: To achieve high coverage of target boxes, a normal strategy of conventional one-stage anchor-based detectors is to utilize multiple priors at each spatial position, especially in scene text detection tasks. In this work, we present a simple and intuitive method for multi-oriented text detection where each location of feature maps only associates with one reference box. The idea is inspired from the twostage R-CNN framework that can estimate the location of objects with any shape by using learned proposals. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…To alleviate this problem, anchor-based methods have been proposed to enhance text localization performance. Deng et al [16] proposed a real-time scene text detector using learner anchors. The method detects the location of an object of any shape by using learned proposals.…”
Section: A Regression/anchor-based Methodsmentioning
confidence: 99%
“…To alleviate this problem, anchor-based methods have been proposed to enhance text localization performance. Deng et al [16] proposed a real-time scene text detector using learner anchors. The method detects the location of an object of any shape by using learned proposals.…”
Section: A Regression/anchor-based Methodsmentioning
confidence: 99%
“…In the task of pedestrian detection, Fang et al found that geometric constraints of pedestrians can be combined with anchor frame information, and anchors containing geometric constraints are used to reduce reasoning time and reduce the error rate of reasoning in pedestrian detection [ 52 ]. Deng et al used the learned proposals in the two-stage R-CNN to propose a learnable anchor and replaced the learnable anchor with the fixed anchor in the one-stage to achieve real-time scene text detection [ 53 ]. In the object detection task of optical remote sensing images, BAO et al proposed two regressions of anchors that adapt to different IOU thresholds according to the different needs of recognition and positioning [ 54 ].…”
Section: Related Workmentioning
confidence: 99%
“…Scene text detection is the process of accurately localizing text instances in wild images; it is an essential component that enables various practical applications such as text recognition, blind navigation, and topological mapping to name a few [1,2]. While recent text detection methods [3][4][5][6][7][8][9] have shown reliable performance on horizontal and multi-oriented text, accurate detection of texts in an arbitrary geometric layout is still an open-ended problem.…”
Section: Introductionmentioning
confidence: 99%